SMS Quizzes with Prizes in the Mass Media: An Analysis of the Indonesian Ulema Council Fatwa Number 9 of 2008 - Fadhli Nur; Mulham Jaki Asti (PAREWA SARAQ: JOURNAL OF ISLAMIC LAW AND FATWA REVIEW, 2022)
This study analyzed Indonesian Ulema Council (MUI) fatwa number 9 of 2008 to explore the legality of SMS quizzes with prizes in the mass media. It aims to describe and analyze the law of SMS quizzes with prizes. The library study was adopted, which is the method of collecting data through libraries, books, reading, taking notes, and processing materials. According to the results, the MUI fatwa method in formulating the law of the SMS quizzes with prizes was based on the book of Allah and did not conflict with the benefit of the people. This is evident by the majority of the legal precedents used to formulate the law on the prohibition of these SMS quizzes with prizes referring to the Qur’an. In this case, its form is already included in the prohibited game because there was an element of gambling. When analyzed from the perspective of Uşūl Fiqh, it was included in the sadd al-żarī'ah rules. The prohibition was based on the arguments of the Qur’an, in which some verses explained the prohibition of gambling. Therefore, the decision to ban the game was an appropriate step because there were indications of gambling in the procedure, which negatively impacted society. A follow-up from the government is needed because the MUI has set prohibitions on the game, which contain gambling elements and are very detrimental to the community.